Die Arbeitsverwaltung als Versicherungskonzern? Zum betriebswirtschaftlichen Umbau einer Sozialbehörde - Hielscher, Volker (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2007)
One of the main pillars of the German social security system, the Federal Labour Agency has undergone the most extensive reorganization of a public sector organisation in Germany in recent years. The contribution describes the main principles of this management-driven reform process and its conseguences for the service quality in the local job centres. It leads to the conclusion that a gain of efficiency in labour administration faces problems of exclusion for specific groups of job seekers from measures of active labour market policy.